2017
DOI: 10.1017/s1751731116002251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of grape seed extract on the growth performance, lipid profile, antioxidant status and immune response of broiler chickens

Abstract: Grape seed extracts (GSE) contain several beneficial bioactive constituents; therefore, can be utilized as a potential feed additive in broiler chickens. An experiment was conducted to investigate the effect of supplementation of broiler chicken diets with GSE as a natural antioxidant at levels of 125, 250, 500, 1000 and 2000 ppm on the growth performance, serum lipid profile, liver glutathione-reduced, thigh muscle malondialdehyde and humoral immune response against Newcastle disease virus vaccines. This expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…In broiler chickens, GSE dietary supplementation has been demonstrated to be an immunostimulant agent [27,28] and to improve fatty acid profile in liver [29]. In hens, it was also able to modulate egg quality and composition and laying performance [30,31], (supplementation for 5 weeks) and to prevent the ovarian aging process [32].…”
Section: Introductionmentioning
confidence: 99%
“…In broiler chickens, GSE dietary supplementation has been demonstrated to be an immunostimulant agent [27,28] and to improve fatty acid profile in liver [29]. In hens, it was also able to modulate egg quality and composition and laying performance [30,31], (supplementation for 5 weeks) and to prevent the ovarian aging process [32].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Hughes et al (2005) reported that BW decreased when broilers fed GSE. While, Farahat et al (2017) found no significant differences were observed in the growth performance and percent livability of broiler chickens when they used GSE at levels of 125, 250, 500, 1000 and 2000 mg/kg diet as compared to the control group. In the respect of GTE, the results are consistent by Erener et al (2011) and Shahid et al (2013), who showed a positive effect on the growth performance of broiler chickens fed 200 mg GTE/kg diet.…”
Section: Productive Performancementioning
confidence: 79%
“…Regarding the blood biochemical parameters, Hajati et al (2014) indicated that addition of 450 mg GSE/kg to broiler diet decreased total cholesterols, triglycerides, LDL and vLDL. In contrast, Farahat et al (2017) observed no significant differences in the total lipid, HDL and vLDL, when broilers were supplemented with GSE or butylated hydroxytoluene (BHT) as compared to the control group. Also, they reported that total cholesterol and LDL were significantly decreased after broilers intake of dietary GSE compared to BHT.…”
Section: Hematological and Biochemical Parametersmentioning
confidence: 81%
See 2 more Smart Citations